2023
DOI: 10.1108/ejim-10-2022-0570
|View full text |Cite
|
Sign up to set email alerts
|

Robotic process automation: bibliometric reflection and future opportunities

Abstract: PurposeRobotic Process Automation (RPA) is a digital transformation tool that demonstrated tremendous growth in research output as well as its application in the past decade. This study attempts to identify essential research gaps and proposes future research agendas in the field by analyzing publishing trends, major stakeholders (authors, countries, affiliations, journals), key clusters and evolving themes by mapping the most recent research (2016–2022) in the field.Design/methodology/approachPreferred Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…The educational process after the pandemic is characterized by a much more frequent use of digital technologies in education, which are constantly evolving and supplemented [25] education, as the use of digital tools provides wide access to student learning, provided that they are accessible [26], [27]. Digital transformation requires large-scale changes, a common vision of the participants in the educational process, and work on the effectiveness of the use of digital technologies in the educational process [28], [29], [30]. Further research is needed to better understand the impact of virtual reality technologies and the use of drones, including the study of the impact on the psychological and pedagogical aspects of the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…The educational process after the pandemic is characterized by a much more frequent use of digital technologies in education, which are constantly evolving and supplemented [25] education, as the use of digital tools provides wide access to student learning, provided that they are accessible [26], [27]. Digital transformation requires large-scale changes, a common vision of the participants in the educational process, and work on the effectiveness of the use of digital technologies in the educational process [28], [29], [30]. Further research is needed to better understand the impact of virtual reality technologies and the use of drones, including the study of the impact on the psychological and pedagogical aspects of the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…RPA is a digital transformation tool that has demonstrated tremendous growth in research output as well as its application in the past decade [11,12]. In response, the dispatch watchman faces periodic repetitive tasks, including downloading attachments, editing daily reports, sending emails, sending SMS, receiving message notifications, and so on.…”
Section: Process Automationmentioning
confidence: 99%
“…(Thekkethil et al .,2021) Kaswan's study showed the implementation of RPA increases work productivity by reducing headcount by assigning responsibility to robot workers, which reduces operational costs and makes jobs more efficient and accurate. (Kaswan et al .,2023) Although a literature review suggested that RPA offers many benefits and opportunities such as business improvement efficiency ; ( Fernandez et al,2023) and increased productivity while relieving employees of redundant, routine tasks, Eura's (2020) study showed some opposite results, three daily routine tasks were Research also indicates that 73% of compliance officers believe that following the RPA will help to improve compliance by reducing expensive FTEs and raising compliance quality, in addition to promoting productivity by eliminating boring tasks and involving employees in work that requires human intelligence. (Ashtikar and Humbad.,2022) Maček's study showed that the RPA is programmed to complete repetitive and labor-intensive tasks.…”
Section: Robotic Process Automation and Work Productivitymentioning
confidence: 99%
“…1-There are three main Justifications for conducting this research that were determined through previous studies and the exploratory study:  There is a limited number of documented studies on global databases conducted on the RPA system around the world and its impact on activities and performance. (Fernandez et al,2023)  Despite the importance of the RPA system in improving the level of productivity, its application in the banking industry remains in its early stages. (IBS Intelligence, 2019&Kumar and Balaramachandran.,2018)  The initiative of Misr Bank to implement the RPA system is considered the first in Egypt, despite its relative newness, within the limits of what the researcher found through the exploratory study.…”
Section: Research Justificationsmentioning
confidence: 99%